Nutritional follow-up in patients with ischemic stroke: With a screening test or with blood parameters? (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the nutritional status of stroke patients and to investigate the value of screening tests and blood parameters in nutritional status follow-up.Material and Methods: This study was conducted on 42 patients who were hospitalized with ischemic stroke. Mini nutritional assessment (MNA) test was performed at admission to all patients. Personalized oral nutritional support was initiated in patients with malnutrition risk (MNA score 24) or malnutrition (MNA score 17). During the first visit, albumin, prealbumin, C - reactive protein (CRP), total cholesterol and hemogram tests were examined. After four weeks follow-up, MNA test and blood tests were repeated in all patients included in the study. Data at baseline and at the end of four weeks were compared. Results: The mean MNA score was 22.44±3.13 at first visit. 15 patients (35.7%) were found to be at risk of malnutrition and 7 (16.6%) were malnourished at admission. Serum albumin and prealbumin levels were significantly lower in patients with abnormal nutritional status (p0.05).Conclusion: The nutritional status of stroke patients should be evaluated at regular intervals after the admission and optimal nutrition plan should be made. MNA scoring is a safe method for both diagnosis and monitoring of malnutrition.Keywords: Ischemic stroke; malnutrition; mini nutritional assessment; blood parameters.
Keywords: Ischemic stroke; malnutrition; mini nutritional assessment; blood parameters.